Forest Carbon Stock Assessment of the Musk Deer National Park, Azad Jammu and Kashmir (AJK) - Qasim, M. (Journal of Tropical Forestry and Environment, 2017)
To tackle with the increasing challenges of climate change, forests are considered as a viable option. Schemes such as Reduced Emissions from Deforestation and Forest Degradation Plus (REDD+) are regarded as financial ventures for not only tackling climate change but also conserving forestry resources and for alleviating poverty. Such schemes however require the exercise of forest carbon stock assessments. It is therefore essential to understand the dynamics of carbon stocks in various forest ecosystems. The study therefore was conducted to assess the carbon stocks of the forests of Musk Deer National Park, AJK. Standard methods were used to calculate the carbon stocks of the Musk Deer National Park. The results revealed that the sampled area of the park contained mean carbon stocks per hectare (ha) of 44.64 ± 12.44 Mg ha-1. The Picea smithiana with 25.40 ± 14.53 Mg ha-1 had the highest of the mean carbon stocks per ha followed by Abies pindrow which had the mean carbon stocks per ha of 17.77 ± 11.80 Mg ha-1. The study was the first attempt, to the extent of my knowledge, for forest carbon stock assessment of the Musk Deer National Park. The results can be helpful in developing REDD+ projects in future, which can assist in forest resource conservation and poverty alleviation. Keywords: Carbon Stock, forest and climate